Floristic study of AqDagh sanctuary in Marakan protected area: west Azarbaijan province, Iran - Hanieh Nafisi; Farrokh Ghahremaninejad (تاکسونومی و بیوسیستماتیک, 2015)
AqDagh sanctuary with the area 5184.7 hectares area is one of the three sanctuaries in the Marakan protected area, in west Azarbaijan province. It is located in the semi-dry to cold semi-dry climates. In this research, 227 taxa (species, subspecies and varieties) belonging to 47 families and 166 genera were identified during 2008 through 2009. Among the studied plants, 205 dicots and 21 monocots and one gymnosperm were recognized. Asteraceae (with 30 species) and Lamiaceae (with 26 species) were the largest families followed by Brassicaceae, Caryophylaceae and Fabaceae. Astragalus (with 9 species) and Gallium (with 5 species) were the most diverse genera. Twenty one endemic and 6 rare taxa plus 2 monotypic genera were identified in the studied area. In addition, 11 taxa from northwest of Iran and 29 from west Azarbaijan were reported for the first time. Therophytes (with 36.57%) comprised the most dominant life form, followed by hemicryptophytes (with 27.75%) in this area. From the chorological point of the view, most of the flora has been influenced by the IT (31.53%) and IT-ES (27.49%) elements. The highest proportion of vegetation in this area belonged to bi-tri or pluriregional elements (with 59.01%).